A New Combination in Oxygraphis Bunge (Ranunculaceae) - Bennet, S. S. R.; Chandra, Sumer (Indian Forester, 1982)
The correct name of Oxygraphis polypetala Hook. F. & Thoms. Is Oxygraphis endlicheri (Walp.) Bennet & Chandra.